The Federal Trade Commission's Report on National Wealth and Income - Dickinson, Z. Clark (Quarterly Journal of Economics, 1927)
Journal Article The Federal Trade Commission's Report on National Wealth and Income Get access Z. Clark Dickinson Z. Clark Dickinson University of Michigan Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 42, Issue 1, November 1927, Pages 117–130, https://doi.org/10.2307/1885367 Published: 01 November 1927